L’apport des images satellitaires dans l’étude des dynamiques de l’occupation du sol des villes d’Amérique Latine - Anne Collin Delavaud (Cybergeo)
Starting with a group of very different cities from the same cultural region, Latin America, a team of young social scientists, thanks to satellite images, obtain a great deal of original material on urban land use and the spatial transformation of the peri-urban area to integrate it with other data for research for a PHD in social sciences with the objective of being operational.